Morning glories (2010), volume 3 ebook - Spencer, Nick (Morning Glories (2010), 2015)
The critically acclaimed smash hit series rolls on with this collection of the blockbuster third arc, 'P.E.!' The first days were just the beginning - when the faculty cancel classes and send the students on an outing in the nearby woods, all hell breaks loose - sending the Glories on a mysterious journey through time and space. Nothing is what it seems to be as Academy's hold on the kids collapses and new threats emerge! Collects MORNING GLORIES #13-19. Author: Nick Spencer. Illustrator: Joe Eisma, Rodin Esquejo . 2012 Nick Spencer & Joe Eisma.